Analysis of the Factors of Spatial Placement of Logistics Facilities - Mikhail V. Kizimirov; Evgenii V. Chernyaev (Регионология)
Introduction. The topic of the study is relevant because it examines key aspects of society and the economy, the understanding of which helps to make informed decisions about the location of logistics facilities and contributes to the development of an effective and sustainable logistics system. The aim of the paper is to examine the spatial distribution of logistics facilities, to identify the factors that influence their location and to present the methodological foundations that determine such a distribution.